Wear and corrosion interaction of AISI D2 in an acidic environment - Garcia Ramos, Tania; Zeinert, Andreas; Muhl, Stephen; Lejeune, Michaël (Tribologia - Finnish Journal of Tribology, 2021)
The tribological, electrochemical and tribo-electrochemical behavior of bare AISI D2 was studied. The tribological aspects were tested by pin on disc with an aluminum oxide ball as counter body, the electrochemical tests were performed in an aqueous solution of citric acid and the tribo-electrochemical evaluation was through a combination of both tests. AISI D2 steel presented abrasive wear in dry and wet conditions, such type of wear occurred due to stick-slip motion, moreover, in wet conditions the alloy corroded at corrosion current values around 10-6 A/cm2. The damage produced over the wear track was larger under wet conditions than for the dry conditions.